IDENTIFY THE CHARACTERISTICS OF LIVESTOCK IN DETERMINING THE SELLING PRICE OF BUFFALO IN SIBORONGBORONG SUBDISTRICT TAPANULI NORT DISTRICT - S Panjaitan; I Sembiring; E Mirwandhono; ND Hanafi ``; Hamdan (Jurnal Peternakan Integratif, 2017)
This study objective was to determine the effect of livestock characteristics in determining the selling price of buffalo in the Subdistrict Siborongborong, North Tapauli District, starts from April to May 2017. The sampling method used is Proportional Stratified Random Sampling. This study used primary data obtained from observation and interview respondents and secondary data obtained from the relevant agencies such as the Institution Central Bureau of Statistics and the Department of Agriculture of North TapanuliDistrik. Respondent of decide snowball sampling method that has 74 respondents obtained from the Villagesuch us : Pohan Jae 18 respondents, Village Siborongborong II 12 respondents, Village LobuSiregar II 17 respondents, Village Siaro 12 respondents, Village Silaitlait 8 respondents, Village SitabotaboDolok 3 respondents, Village sitabotaboToruan 4 respondents. The parameters studied were the characteristics of livestock that is horn, the location of feather vortex and the amount of vortex of feathers to the selling. Data analysis in this study is to see the relation of the selling price and characteristics of buffalo, in using multiple linear regression analysis.The result of research indicates that the habit of Batak Tribe society in using buffalo as one of the ceremony of traditional ceremony gives influence to the difference of buffalo selling price mast influence amoung parameters to selleng price buffalo is horn , The location of the feather vortex and the amount of feather vortex in Siborongborong Sub-district, North Tapanuli regency North Tapanuli District.